2015
DOI: 10.1039/c5nj01876e
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium, kinetic and thermodynamic adsorption studies of organic pollutants from aqueous solution onto CNT/C@Fe/chitosan composites

Abstract: The adsorption of organic pollutants, including dyes (methylene blue (MB) and methyl orange (MO)), antibiotics (tetracycline (TC)), and organic arsenical compound (roxarsone (ROX)), has been studied on a new kind of CNT/C@Fe/CS nanocomposite. The effect of solution pH, contact time, and temperature on adsorption properties has been studied. The adsorption process follows the pseudo-second-order kinetic model very well, and equilibrium studies fit well with Langmuir, Freundlich, and Temkin adsorption isotherms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 36 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Among the available adsorbents, carbon nanotubes (CNTs) have been regarded as a promising and efficient adsorbent due to their large specific surface area (SSA), porous nanostructure with a high π-electronic density, and ease of functionalization . However, the separation of nanosized CNTs has become a problem because of their nanotoxicity , and secondary pollution after adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Among the available adsorbents, carbon nanotubes (CNTs) have been regarded as a promising and efficient adsorbent due to their large specific surface area (SSA), porous nanostructure with a high π-electronic density, and ease of functionalization . However, the separation of nanosized CNTs has become a problem because of their nanotoxicity , and secondary pollution after adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…This has raised concerns about arsenic contamination, especially in conversion of ROX to inorganic forms. Among the various remediation methods, adsorption-based removal is a promising strategy for the controlled uptake of inorganic and organic pollutants. There are limited examples of adsorbents used for ROX removal that include carbon nanotubes, , chitosan composites, montmorillonite, metal oxides, , goethite composite, and metal–organic frameworks . By contrast, chitosan is an abundant and low-cost adsorbent that has been investigated mainly by batch techniques. , Poon et al reported batch equilibrium studies of glutaraldehyde (GA) cross-linked chitosan powders with ROX, where cross-linking was shown to enhance the adsorption capacity of ROX from 0.55 to 0.98 mmol/g .…”
Section: Introductionmentioning
confidence: 99%
“…These values are within error of reported saturation capacities for other engineered microplastics and magnetic composites developed for the adsorption of organic pollutants. [33,38] However, the B max of all the MNM systems are lower than those reported for other carbon-based materials, specifically a couple orders of magnitude lower than activated carbon. [39,40] The Langmuir adsorption coefficients obtained for the CMA MNMs, QMA MNMs, and PEG MNMs are 1.20, 1.28, and 1.84 nM, respectively.…”
Section: Resultsmentioning
confidence: 73%
“…This plateau is also known as the equilibrium monolayer capacity. [33] In order to understand the behavior of the synthesized microparticles, the Langmuir model is used to fit the experimental data and obtain the maximum adsorption capacity (B max ) and Langmuir adsorption coefficients (K D ) for each system (presented in Table 2). According to the values of nonlinear R 2 presented in Table 2, the Langmuir model provides a good fit to describe the systems and suggests the adsorption process is homogeneous and occurs as a monolayer, implying there is no interactions between PCB molecules bound at the surface of the MNMs.…”
Section: Resultsmentioning
confidence: 99%